Consequences of physical distancing emanating from the COVID-19 pandemic: An Australian perspective (2020)
The sobering reality of the COVID-19 pandemic is that it has brought people together at home at a time when we want them apart in the community. This will bring both benefits and challenges. It will affect people differently based upon their age, health status, resilience, family support structures, and socio-economic background. This article will assess the impact in high income countries like Australia, where the initial wave of infection placed the elderly at the greatest risk of death whilst the protective measures of physical distancing, self-isolation, increased awareness of hygiene practices, and school closures with distance learning has had considerable impact on children and families acutely and may have ramifications for years to come.